Katalysatorscreening und Reaktormodellierung für die oxidative Methankopplung zur Brennwertanhebung von Biogas. Issue 6 (27th April 2017) - Friedel, Marcus; Nitzsche, Jörg; Krause, Hartmut
Abstract: The feed of biogas into the natural gas grid contributes to the success of the energy transition from fossil and nuclear fuels to renewables, because the usage of fed‐in biogas is highly diversified. But the necessary admixture of liquefied petroleum gas (LPG) to increase the heating value results in high costs and in a dependency on fossil fuels. Currently, the process of the oxidative coupling of methane to produce higher hydrocarbons from biogas, whereby an independent increase of the heating value will be possible, is investigated.